The impact of information and communication technology on human capital in Algerian companies - BOUGUESRI Sarra (Journal of North African Economies, 2025)
The aim of this study is to investigate the impact of information and communication technology (ICT) in Algerian Companies' human capital (HC). The data was collected from 120 employees by means of a questionnaire. Statistical techniques such as descriptive statistics , ANOVA test, correlation and multiple regressions were employed. To confirm the suitability of data collection instrument Cronbach’s Alpha was used. The present study found that the use of ICT will help the company to increase their human capital’s performance . So the topic area of information and communications technology (ICT) has now become a regular feature in enhancing the role of human capital in the company .